2018
DOI: 10.1021/acs.cgd.8b00298
|View full text |Cite
|
Sign up to set email alerts
|

Position of Methyl and Nitrogen on Axial Aryloxy Substituents Determines the Crystal Structure of Silicon Phthalocyanines

Abstract: Phthalocyanines are a class of organometallic compounds that have been investigated extensively for emerging applications such as organic photovoltaics, organic light-emitting diodes, and thin-film transistors. For these applications, the understanding of molecular structures and intermolecular interactions is extremely crucial and is one of the most promising pathways for designing a new generation of functional materials. Here, the crystal structures of six axially substituted silicon phthalocyanines (SiPcs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…16,48 Intermolecular interactions can be further enhanced to improve charge transport mobility, however these interactions are not necessarily related to electron donating or withdrawing character of functional groups. 10,13,15 While μ e of materials 3 and 4 are relatively low compared to state-of-the-art MPc and R 2 -SiPc materials, these observations confirm that designing R 2 -SiPc materials with stronger electron-withdrawing groups result in OTFTs with lower V T . Confirming that this trend continues to hold with stronger electron-withdrawing pendants will enable the design of next-generation R 2 -SiPcs with a combination of high μ e and low V T by further tuning pendant groups to optimize intermolecular interactions and electronic coupling 16,49 while incorporating electron-withdrawing moieties to reduce V T .…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…16,48 Intermolecular interactions can be further enhanced to improve charge transport mobility, however these interactions are not necessarily related to electron donating or withdrawing character of functional groups. 10,13,15 While μ e of materials 3 and 4 are relatively low compared to state-of-the-art MPc and R 2 -SiPc materials, these observations confirm that designing R 2 -SiPc materials with stronger electron-withdrawing groups result in OTFTs with lower V T . Confirming that this trend continues to hold with stronger electron-withdrawing pendants will enable the design of next-generation R 2 -SiPcs with a combination of high μ e and low V T by further tuning pendant groups to optimize intermolecular interactions and electronic coupling 16,49 while incorporating electron-withdrawing moieties to reduce V T .…”
Section: Resultssupporting
confidence: 57%
“…In this previous work, we observed a range of isotropic and anisotropic thin-film morphologies and found that anisotropic grain structures across the substrate enabled by favorable film growth was a greater driver of μ e than axial group selection. Additionally, DFT calculations have demonstrated that intermolecular electronic coupling has a strong impact on theoretical field-effect mobilities, making it a good predictor for high-mobility R 2 -SiPc materials as polycrystalline thin-films in devices. , Intermolecular interactions can be further enhanced to improve charge transport mobility, however these interactions are not necessarily related to electron donating or withdrawing character of functional groups. ,, While μ e of materials 3 and 4 are relatively low compared to state-of-the-art MPc and R 2 -SiPc materials, these observations confirm that designing R 2 -SiPc materials with stronger electron-withdrawing groups result in OTFTs with lower V T . Confirming that this trend continues to hold with stronger electron-withdrawing pendants will enable the design of next-generation R 2 -SiPcs with a combination of high μ e and low V T by further tuning pendant groups to optimize intermolecular interactions and electronic coupling , while incorporating electron-withdrawing moieties to reduce V T .…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The highest reported electron mobility (μ e ) for n-type SiPcs is ∼0.5 cm 2 V –1 s –1 from F 10 -SiPc ( 3 , Figure ), which is comparable or exceeds that of MPcs in n-type OTFTs, implying the potential of this class of MPcs to rival other state-of-the-art n-type organic semiconductors. , Despite this excellent potential, only a few structure–property relationships have been established to determine the impact of the axial substituents on SiPc OTFT performance. Several studies indicate that the choice of the axial group affects SiPc packing in the single crystal, often changing the π–π stacking distance, herringbone angle, and degree of molecular overlap. , To this end, Gali et al demonstrated that density functional theory (DFT) calculations in combination with kinetic Monte Carlo simulations could be used to screen the potential of several compounds by estimating mobility and its directionality and identified compound 9 (3I-SiPc), which has never been previously incorporated into OTFTs, as possessing better 1D single-crystal charge transport and compound 3 (F 10 -SiPc) as the best for 2D single-crystal charge transport . Melville et al found that increasing the size of the molecular pendant decreased mobility for carboxyl-functionalized SiPcs 10 (PhCOO-SiPc) and 11 (NpCOO-SiPc) and their anthracene-substituted analogues in OTFTs .…”
Section: Introductionmentioning
confidence: 99%